Chile : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This report assesses the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) in Chile. Banking secrecy provisions continue to limit the ability of Chile to investigate and disclose potential money laundering offences and, thereby, to provide effective international cooperation through the financial intelligence unit. Provisions are available for mutual legal assistance but they are cumbersome. The expanded AML/CFT regime introduced by Law 19.913 is too recent to permit any conclusions about the effectiveness of its implementation.